Preventing cardiovascular disease: Participant perspectives of the FAITH! Program. (October 2019) - Brewer, LaPrincess C; Morrison, Eleshia J; Balls-Berry, Joyce E; Dean, Patrick; Lackore, Kandace; Jenkins, Sarah; Cohen, Consuelo; Johnson, Jacqueline; Ellis, Frances; Mangum, DC; Hayes, Sharonne N; Patten, Christi
Striking cardiovascular health disparities exist among African-Americans in Minnesota compared to Whites; however, community-based interventions to address cardiovascular disease risk are lacking. This study explored participant perceptions of a culturally tailored, cardiovascular disease prevention program developed using a community-based participatory research process. Research participation perceptions, program benefits, and program satisfaction/acceptability were analyzed using a mixed-methods approach. Overall, acceptability was high. Findings highlight the favorable inclusion of African-Americans (research perception), knowledge gained about healthy lifestyle practices (benefits), and quality of the curriculum/speakers (satisfaction). Community-based participatory research may be useful in fostering the acceptability of behavior change interventions among marginalized African-American communities.